A non-fasting marker of metabolic syndrome in a high-risk population - Sabrina Cancelliere; Tracy Heung; Christina Blagojevic; Sarah Malecki; Satya Dash; Anne S. Bassett (The Journal of Nutrition, Health and Aging, 2025)
Objective: The rising prevalence of metabolic syndrome among young adults has prompted studies of fasting triglyceride-glucose (TyG) index as a marker of insulin resistance. We aimed to evaluate metabolic syndrome in young adults using non-fasting TyG index and a high-risk genetic model, 22q11.2 microdeletion. Methods: We assessed metabolic syndrome and its components in 350 adults (50.6% female) aged 18–59 (median 27.7, IQR 22.5–38.1) years with typical 22q11.2 microdeletions. We used multivariable logistic regression and receiver operating characteristic (ROC) curves to evaluate the association of non-fasting TyG index with metabolic syndrome. Results: Non-fasting TyG index was significantly associated with metabolic syndrome (OR 3.23, 95% CI 2.27–4.59, p < 0.0001), independent of age, sex, BMI, and hypothyroidism. Non-fasting TyG index was positively correlated with number of metabolic syndrome components per individual. In this high-risk population, prevalence of metabolic syndrome was 21.7% (60/277) among young adults (18−39 years), and 45.2% (33/73, p < 0.0001) among middle-aged adults (40−59 years). Non-fasting TyG index ≥4.81 was an effective indicator of prevalent metabolic syndrome, with an area under the ROC curve of 0.83 (95% CI 0.78−0.88). Conclusions: The results support non-fasting TyG index as a practical marker of metabolic syndrome, and by extension insulin resistance, encouraging future studies evaluating non-fasting TyG index in young adults as a predictor of cardiovascular disease later in life. The high prevalence of metabolic syndrome at a young age in 22q11.2 microdeletion demonstrates the potential value of this genetic high-risk population for future prospective studies, with animal and cellular models available.